Un compuesto de 113m In para múltiples usos diagnósticos - Noto, María Gracia; Gónzalez Toledo, E.; Palcos, María Cristinia; Nowotny, Gustavo Adolfo; Nicolini, Jorge O. (1977)
Fil: Noto, María Gracia Comisión Nacional de Energía Atómica; Argentina